Promosi Kesehatan dalam Melakukan Pencegahan Penyakit Degeneratif pada Remaja - Rovica Probowati; Insanul Firdaus; Andriani Mei Astuti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Degenerative diseases are chronic diseases that affect a person's quality of life. There are various degenerative diseases that should be treated as early as possible, such as diabetes mellitus, high blood pressure, heart stroke and other degenerative diseases. Indonesia bears a double burden of disease in the health sector, namely infectious diseases are still rampant and coupled with chronic degenerative diseases. Efforts to promote health are very important in efforts to prevent degenerative diseases in adolescence. This health promotion is carried out in adolescents because of the unhealthy lifestyle of adolescents, this can be seen from the smoking habits of adolescents and the habit of eating unhealthy foods or snacks carelessly, lack of consumption of vegetables and fruits, and minimal physical activity such as sports in efforts to prevent degenerative diseases in adolescents. The purpose of this activity is to increase knowledge about the prevention of degenerative diseases among adolescents and as an effort to overcome the problem of the emergence of degenerative diseases in adolescence. The results of community service activities show an increase in average knowledge from 6.61 to 13.80 and an increase in attitudes from 9.61 to 14.47. Community service activities can be carried out well, this is seen from the smooth running of the event and the participation of teenagers. Improving the quality of health needs to be done by raising awareness and increasing education for teenagers about preventing degenerative diseases.